واقع تطبيق مبادئ إدارة الجودة الشاملة في البرامج التدريبية للمنظمة الصناعية(دراسة حالة شركة نسيج اللاذقية) - ابراهيم حسين; طرابلسيّة شيراز; عبد الحميد فاطمة حاتم (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت هذه الدراسة إلى التعرف على واقع تطبيق مبادئ إدارة الجودة الشاملة في البرامج التدريبية في شركة نسيج اللاذقية، بالإضافة إلى التعرف على المشكلات التي تحول دون تطبيقها في الشركة. ولقد قامت الباحثة بإعداد استبيان وتوزيعها على عينة البحث التي بلغت (33) فرداً من المدرِّبين العاملين في الشركة، كما قامت بإجراء مقابلات مباشرة مع بعض المديرين، ومع بعض العاملين الذين تلقوا دورات تدريبية في الشركة. وتوصلت الباحثة إلى مجموعة من النتائج كان من أهمها: - تحتوي الشركة قسماً لإدارة الجودة والذي يعنى بجودة المنتج النهائي الذي يقدم للمستهلك ويحقق رضاه فحسب، ولكنها لا تحتوي قسماً لإدارة الجودة الشاملة لكامل نشاطات الشركة. - على الرغم من عدم وجود قسم خاص بإدارة الجودة الشاملة في الشركة، إلّا أنّ الإدارة العليا تدعم البرامج التدريبية، كما يتم اختيار المتدربين بناءً على احتياجاتهم التدريبية، واختيار المدربين بناءً على الكفايات والمهارات المطلوبة. - لا تقوم الشركة بإشراك المتدربين في تصميم البرامج التدريبية، واتخاذ القرارات المتعلقة بها. - توجد مشكلات كبيرة تحول دون تطبيق مبادئ إدارة الجودة الشاملة في البرنامج التدريبي للشركة، تتمثل أهمها بالمركزية في الإدارة وعدم تفويض الصلاحيات، إضافةً إلى كثرة الأعباء والأعمال الملقاة على عاتق المدربين إضافة إلى عملهم في التدريب مما يجعلهم مشتتين وغير قادرين على التركيز بالشكل المطلوب الذي يحقق الجودة المطلوبة. ولقد أوصت الباحثة بضرورة إحداث قسم خاص بإدارة الجودة الشاملة في الشركة، وإخضاع العاملين لدورات مكثفة بإدارة الجودة الشاملة، إضافةً إلى منح الصلاحية والثقة والتحفيز لجميع أعضاء الفريق التدريبي، لاتخاذ القرارات الخاصة بإعداد البرنامج التدريبي وتنفيذه وتقويمه. This study aimed at identifying the reality of the application of the principles of total quality management in training programs in Textile Co., Lattakia, as well as to identify problems that prevent its application in the company. The researcher prepared a questionnaire and distributed it to the research sample, which amounted to (33) members of the trainers who are working in the company. She also conducted in-direct interviews with some managers, and some workers who have received training in the company. The researcher found a set of results, the most important of them was: - The company contains a section of the company’s quality management, which means the quality of the final product, which provides to consumer to achieving his satisfaction only, but it does not contain a section of total quality management for the entire company’s activities. - the high management supports training programs, as the trainees are selected on the basis of their training needs، and choosing of the trainers based on the competencies and skills required. - The company does not involve trainees in the design of training programs، and decision-making related to them. - There are great problems prevent the application of the principles of total quality management in the training program for the company، the most important of them was centralized management and the lack of devolution of powers، in addition to the many burdens and business entrusted to the trainers in addition to their work in training، makes them distracted and unable to focus properly investigating the required quality. The researcher recommended the need to make a special section of TQM in the company, and subjecting workers to intensive courses in TQM, in addition to granting authority, confidence and motivation to all members of the training team, to make decisions for the preparation of the training program, implementation and evaluation it.